METHODS OF HARVESTING AND STORING QUINCE FRUIT (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2024)
The article scientifically discusses the determination of the ripening period of quince fruits, their placement in boxes, and the sorting process before storage. During the storage period, some of the fruits show a decrease in quality indicators, while others show an increase, as shown in the table. The article also presents various storage methods for quince, along with the optimal air humidity and temperature for its storage.